Study of the Impediments to Effective implementation of DOST Agency’s "Single Entry Point” mechanism in Azerbaijan - Alizade, Afag; Yashar, Narmin; Narimanova, Nisa (ADA University, 2023)
One of the fundamental reasons behind the existence of public organizations is to provide services to individuals. In this regard, public organizations are doing their best to ease the access to the public services. DOST Agency’s single entry point mechanism is one of the vivid examples for this. This capstone project is dedicated to evaluating this mechanism, finding the impediments to effective implementation of it and most importantly bringing the world experience to eliminate those barriers. The study has revealed that though single-entry point system somehow eased the burden of citizens to get the services, partially eliminated public officials-citizens direct communication, there are some issues regarding its implementation, including poor accessibility to services, non-compliance of some services to mentioned system as well as lack of individual awareness about the existence of the organization. Given that surprisingly there is not any research conducted to evaluate the single-entry point mechanism implemented by the DOST Agency, and hence, not available data about the mechanism’s issues, both qualitative and quantitative research method have been undertaken to find out impediments to achieve fully effectiveness of mechanism. For this purpose, this study delved into the world experience and identified several measures to be implemented to achieve the full level of effectiveness of DOST Agency’s single entry point mechanism.
Keywords: Public services -- Azerbaijan; Administrative agencies -- Evaluation; One-stop service centers -- Management; Public and International Affairs